Strategi Komunikasi Pemasaran Digital Melalui Instagram dalam Promosi Penerimaan Murid Baru: Analisis Model AIDA pada SMP Islam Al Azhar 55 Jatimakmur - Ropik; Feri Johansah; Arrum Dara Efda (Jurnal Ragam Pengabdian, 2026)
The development of digital technology has significantly transformed marketing communication strategies in various sectors, including education. Educational institutions increasingly utilize social media platforms to promote their programs and attract prospective students. Instagram is one of the most widely used social media platforms due to its visual communication features and high user engagement, making it an effective medium for digital marketing communication. This study aims to analyze the digital marketing communication strategy through Instagram in promoting new student admissions at SMP Islam Al Azhar 55 Jatimakmur using the Attention, Interest, Desire, and Action (AIDA) model. This research employs a qualitative approach with a case study method. Data were collected through in-depth interviews, observation of promotional content on the school's Instagram account, and documentation. Data were analyzed using data reduction, data presentation, and conclusion drawing techniques. The results show that Instagram plays a significant role in supporting the school's promotional activities. Visual content attracts audience attention, information about school programs increases interest, school achievements and facilities build desire, and registration information encourages prospective students to take action. This study concludes that Instagram-based digital marketing communication is an effective strategy for promoting new student admissions in educational institutions.